Validity of predictive score of mortality in peptic ulcer perforation (POMPP) in predicting perforated peptic ulcer mortality operated in Sanglah General Hospital, Denpasar, Bali - I Gusti Putu Agung Pratama Putra; Ketut Sudiasa; Tjokorda Gde Bagus Mahadewa (Indoscholar, 2022)
Introduction: Peptic ulcer perforation is a non-traumatic emergency that is often encountered and gives a mortality rate of up to 70%. The need for a system that is easy and simple in predicting and screening patients in the initial triage to predict the incidence of mortality after surgery is important. This study aim to test the validity of predictive score of mortality in peptic ulcer perforation (POMPP) in predicting mortality in patients with perforated peptic ulcer surgery. Methods: This study was a diagnostic study with 50 peptic ulcer perforation patients operated between February 2019 to February 2020, and collected with consecutive sampling method. All patients who were operated was calculated for the preoperative POMPP scores, with parameters of age, blood urea nitrogen, and albumin. Patients who were deceased or refused to participate were excluded. The best cut-off point was calculated, then sensitivity, specificity, positive and negative predictive value (PPV/NPV), accuracy of score and POMPP score validity were calculated in predicting post-operative patient mortality. Results: The best cut-off value obtained from receiver operating characteristic (ROC) curve was ≥1.5, where patients with POMPP ≥1 were exposed to a high risk of postoperative mortality (80.8%), and POMPP <1.5 had a low risk of postoperative mortality (19.2%). Other scores were calculated as follow: sensitivity 80.7%, specificity 91.6%, PPV 91.3%, NPV 81.4%, accuracy 86% and the validity test score of 50 patients reached 100%. Conclusion: POMPP has good validity and can be used as a screening tool for patients with perforated peptic ulcer surgery.